Basic and clinical study of efficacy and adverse effects of flumatinib in Ph+ ALL - Wang, Jun; Wu, Jiafei; Wang, Yijing; Zheng, Boyue; Wang, Yu; Jiang, Chuanyan; Zou, Mengying; Li, Hui (Frontiers in Pharmacology, 2023)
Objective: To investigate the efficacy and safety of chemotherapy based on flumatinib in treating Ph+ALL. Methods: Clinical data of 29 patients with Ph+ALL who received flumatinib-based chemotherapy in Sichuan Provincial People's Hospital from January 2020 to January 2023 were analyzed. Concentrations of TKI in the peripheral blood, bone marrow, and cerebrospinal fluid of some patients were monitored and analyzed. Cytological experiments were conducted on SUP-B15, a Ph+ALL cell line. Results: A total of 29 patients were included. After flumatinib-based chemotherapy, the induced CR, 3-month CR, and 6-month CR rates were 96.3%, 87.5%, and 86.7%, respectively. The negative conversion rate of MRD was 82.6%, 91.3%, and 95.6% in 1, 2, and 3 months after treatment, respectively, and 4.3% of patients had not achieved negative conversion in 3 months after treatment. The rates of MMR were 73.9%, 87.5%, and 93.3% in 1, 3, and 6 months after treatment, and CMR were 52.2%, 62.5%, and 73.3%, respectively. Among the 29 patients, 11 (37.9%) were transplanted and continued to use flumatinib for one year after transplantation. All patients maintained deep remission up to the time of follow-up. Median follow-up was 12 months (1-33 months), progression-free survival (PFS) was 11 months (1-33 months), and median overall survival (OS) was 12 months (1-33 months). The adverse reactions were mainly myelosuppression, liver insufficiency, and infection, they were generally tolerable. In terms of blood concentration, the highest concentration of flumatinib was found in bone marrow > serum > cerebrospinal fluid in Ph+ ALL bone marrow. In contrast, the concentration distribution of dasatinib and imatinib was serum > bone marrow > cerebrospinal fluid. At the same time, flumatinib can penetrate the blood-brain barrier, while in the patients using Dasatinib in this study, the concentration of cerebrospinal fluid was lower than the lower limit of detection. Compared with Imatinib and Dasatinib, pharmacodynamic analysis of SUP-B15 cells indicated that flumatinib had the most potent inhibitory effect on Ph+ ALL cell lines. Conclusion: Flumatinib combined with chemotherapy has good efficacy and safety in treating Ph+ALL, and flumatinib can cross the blood-brain barrier. Flumatinib was superior to Dasatinib and Imatinib in cell experiments.